Insulin Prevents Aberrant Mitochondrial Phenotype in Sensory Neurons of Type 1 Diabetic Rats - Aghanoori, Mohamad-Reza (Exp Neurol, 2017)
Diabetic neuropathy affects approximately 50% of diabetic patients. Down-regulation of mitochondrial gene expression and function has been reported in both human tissues and in dorsal root ganglia (DRG) from animal models of type 1 and type 2 diabetes. We hypothesized that loss of direct insulin signaling in diabetes contributes to loss of mitochondrial function in DRG neurons and to development of neuropathy. Sensory neurons obtained from age-matched adult control or streptozotocin (STZ)-induced type 1 diabetic rats were cultured with or without insulin before determining mitochondrial respiration and expression of mitochondrial respiratory chain and insulin signaling-linked proteins. For in vivo studies age-matched control rats and diabetic rats with or without trace insulin supplementation were maintained for 5 months before DRG were analyzed for respiratory chain gene expression and cytochrome c oxidase activity. Insulin (10nM) significantly (P<0.5) increased phosphorylation of Akt and P70S6K by 4-fold and neurite outgrowth by 2-fold in DRG cultures derived from adult control rats. Insulin also augmented the levels of selective mitochondrial respiratory chain proteins and mitochondrial bioenergetics parameters in DRG cultures from control and diabetic rats, with spare respiratory capacity increased by up to 3-fold (P<0.05). Insulin-treated diabetic animals exhibited improved thermal sensitivity in the hind paw and had increased dermal nerve density compared to untreated diabetic rats, despite no effect on blood glucose levels. In DRG of diabetic rats there was suppressed expression of mitochondrial respiratory chain proteins and cytochrome c oxidase activity that was corrected by insulin therapy. Insulin elevates mitochondrial respiratory chain protein expression and function in sensory neurons and this is associated with enhanced neurite outgrowth and protection against indices of neuropathy.